Can Rescission Action in Tax Matters Hurt Legal Security? - Melo, Rebeca de Magalhães; Borges, Antônio de Moura (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
In this article we will deal with the rescission action under Tax law, the problem concerns whether the management of this type of action could harm the principle of legal certainty. Does the deconstitution of the judgments occur in the judgment of the rescission actions filed by the National Treasury or by the taxpayer, in this case would it be in conflict with the principles of constitutional supremacy and isonomy, on the one hand and on the other hand, that of legal certainty and respect for res judicata? The purpose of this article is to enable a reflection on the theme in the light of doctrine and jurisprudence, starting from a bibliographic and documentary analysis, noting that in the scope of tax law there is obedience to the principle of strict tax legality and it is discussed in the doctrinal scope to possibility or not of the beneficial retrorativeness of the tax law.